BIOLOGICAL IMPORTANCE AND HEALTH EFFECT OF Perilla frutescence PLANT - Mohammad Asif (Indonesian Journal of Pharmacy, 2012)
The  study  was  designed  to  study  the  Biological  importance and nutritional benefits  of Perilla frutescence  plant. This plant has very  high  biological  activities.  It  contains  various  phytoconstituents  such  as  different  phenolic  compounds  (like rosemarinic  acids,  luteolin  chrysoeriol,  quercetin,  catcehin, apigenin, etc), vitamins,  minerals etc. Perilla seeds contained 30-40%  fixed  oil,  contained  both  saturated  (palmitic  acid  5-7%, stearic  acid  1-3%),  unsaturated  (UFAs)  or  polyunsaturated (PUFAs) (oleic acid 12-22%, linoleic acid 13-20%, γ-linolenic acid 0-1%,  α-linolenic  acid  52-64%,  icosanoic  acid  0-1%)  fatty  acids. Perilla  oil  is  highly  unsaturated  oil  among  the  all  current discovered  natural  vegetable  oils.  Whole  perilla  plant  has  many important  functions  on  improving  and  accelerating  human  health and is effective in prevention of various diseases.Key  words:    Perilla  frutescence,  biological  activities,  phyto-constituents, polyphenols, polyunsatured fatty acids.